Efeito de borda em ecossistemas nativos e plantações de eucalipto sobre dinâmica do carbono no solo - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
To reduce global warming, it is necessary to search for strategies whose purpose is to mitigate the emissions of these gases and their absorption. Just as forests are carbon sinks, microbiota is also involved with carbon storage in the soil. However, as a result of anthropogenic activities, forests are often reduced to fragments, which are strongly subject to the edge effect, receiving much pressure from external factors affecting their functioning. Thus, the objective of the work was to evaluate changes in the organic and microbial carbon stock as well as the microclimate along the edge of six forest fragments. For the evaluation, studies were made in two different forest systems, being three fragments of semi-deciduous Cerrado seasonal forest and three of Eucalyptus spp. planted forests located in the southeast region of Goiás, Brazil The experimental design of random blocks with subdivided plots, each forest being a different block, the transects representing the plots, and the subdivisions corresponding to the edge/interior distance gradients. Each fragment had three transects of 100 meters each, with ten plots forming a gradient of distance from the edge every 10 meters, the plots contain dimensions of 10 x 10 m. The soil and microbiological variables tested were: microbial biomass carbon (CBM), microbial respiration (RM), metabolic quotient (qCO2), total organic carbon, microbial quotient (qMIC %), soil organic matter (MO) and soil gravimetric humidity (Ug%). The microclimatic variables measured were: relative air humidity (%); temperature (°C), wind (km/h), light (lux). The effect of distances was tested by means of a regression. For correlation between all variables correlation was made and finally a principal component analysis (PCA). The two environments are significantly different, the FES are larger carbon sinks, as well as have a greater dynamic balance because of the biodiversity present. As for the effect of external factors inside the fragments, it observes great influence mainly on the local microclimate. But the action on soil microorganisms is also noted. The action of the distance gradient of the edge was observed for the microbiological and microclimatic variables analyzed, for semi-deciduous seasonal forests (FES). Eucalyptus forests, on the other hand, did not respond in the same way as native forests, since the variables studied were little affected by the edge effect. The survey shows that as for the carbon storage in the soil and the action of microbiota, the two types of forests respond differently. Since the FES stored more carbon and were more affected by the distance from the edge than the eucalyptus, this may be related to the hominization of the eucalyptus environment. To this end, it is necessary to conduct more research on the subject in order to better elucidate the results of this study.
Keywords: Florestas Estacionais; Carbono microbiano; matéria orgânica; Gradiente de distância da borda.; Seasonal Forests; Microbial carbon; organic matter; Edge distance gradient; CIENCIAS AGRARIAS